PEMANFAATAN ARSIP DATA LABORATORIUM DALAM ANALISIS POTENSI ANTIBAKTERI EKSTRAK BUAH NANAS (Ananas Comosus) TERHADAP PERTUMBUHAN STAPHYLOCOCCUS AUREUS - Muhammad Aditya Rachman; Annisaturrahmah Himawan (Nusadaya Journal of Multidiciplinary Studies, 2026)
Laboratory data archives play an important role in supporting scientific research, particularly in ensuring data validity and reproducibility. This study aims to analyze the antibacterial potential of pineapple (Ananas comosus) extract against Staphylococcus aureus based on laboratory data documentation. This research employed an experimental method with a disc diffusion technique, supported by archival analysis of laboratory records. The results showed that pineapple extract exhibited antibacterial activity, indicated by the formation of inhibition zones at all concentrations tested. Higher concentrations produced larger inhibition zones, demonstrating a dose-dependent effect. From an archival perspective, proper documentation of laboratory data enables systematic analysis and supports scientific accountability. This study highlights the importance of laboratory archives in strengthening research quality and data reliability.